The Product-Type Operators from Hardy Spaces into nth Weighted-Type Spaces - Ebrahim Abbasi (Abstract and Applied Analysis)
The main goal of this paper is to investigate the boundedness and essential norm of a class of product-type operators Tu,v,φm,m∈ℕ from Hardy spaces into nth weighted-type spaces. As a corollary, we obtain some equivalent conditions for compactness of such operators.